FinTech lenders on the consumer finance market in Central and Eastern Europe - Waliszewski, Krzysztof; Gębski, Łukasz (Przegląd Wschodnioeuropejski, 2024)
The authors analyze the consumer finance markets in the countries of Central and Eastern Europe against the background of the markets of the EU countries and the Euro area, with particular emphasis on non-bank lending institutions that use financial technologies to grant loans to consumers. As research shows, these loans are more expensive than traditional consumer bank loans, but more accessible, more flexible and tailored to the needs of customers from different generations. Black swans – sudden, unpredictable events – do not, in principle, change the demand for consumer credit but merely slow the growth dynamics of the market, which returns to its pre-disruption level after some time.